STRATEGIC POLITICAL COMMUNICATION AND PROPAGANDA: WINNING FACTORS OF PRABOWO SUBIANTO-GIBRAN RAKABUMING RAKA IN THE 2024 ELECTION - Nastain, Muhamad; Safitri, Rindiyani Irfani; Hidayat, Nugraheni Attharika; Agustin, Hesti (Universitas Padjadjaran, 2025)
This article examines the factors that led the Prabowo-Gibran pair to reach the door of victory in the 2024 elections. The twists and turns of the long process can be navigated with various smooth strategies that demonstrate the pair’s expertise in politics, ultimately leading to a one-round victory. This research employs a qualitative descriptive method, utilizing data collection techniques that include a literature study and observation. The results showed that various factors contributed to the Prabowo-Gibran pair’s victory, starting with the role of President Jokowi as an incumbent who had a significant influence on Prabowo-Gibran’s electability, often referred to as the Jokowi Effect. In addition, proficiency in identifying opportunities and managing situations is a key collaboration, such as the formation of “Gemoy” framing, success in reaching Gen Z preferences, and reversing propaganda tactics. The victory was also supported by the TKN’s expertise in gaining the support of various political parties, mass organizations, and volunteers. Effective management of situations and opportunities is key, as well as a strategy to stay one step ahead of rivals to achieve success. This research contributes to the field of political communication and highlights the importance of forming public opinion as a key factor in the success of political contestants in democratic elections.